(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
Environment has acquired paramount significance in contemporary geo-political scenario. Disturbing fluctuations in climatic patterns due to aggravating green house effect have already triggered alarm button in this regard. All the leading nations of the world are focusing their attention on the vital environmental issues which threaten to wreck the very existence of all forms of life from the face of mother earth.